Grammatical colocations verb + preposition in Spanish as a foreign language: contrastive interlanguage analysis in learners of levels A2 and B1 (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This study examines the frequency of grammatical collocations verb + preposition (GramCol v+p) in L1-English learners of Spanish as a Foreign Language (SFL) of levels A2 and B1 under the model of Interlanguage Contrastive Analysis. To this end, a collocational typology based on a criterion of intermediate fixedness was implemented. The results show higher frequency in level B1, but not in the variety of the units, and a greater number of correct uses than in A2. Regarding found differences according to syntactic and semantic pattern, the variables of competence, pattern complexity and theme appear to play an important role in their explanation in the context of the learners’ corpus examined. This work contributes to the study of GramCol v+p and other types (noun/adjective + preposition) in SFL.
Keywords: Grammatical collocations; verb preposition; ICA; SFL; writing skills